Nitrogen‐fixing trees have no net effect on forest growth in the coterminous United States. (20th October 2020) - Staccone, Anika P.; Kou‐Giesbrecht, Sian; Taylor, Benton N.; Menge, Duncan N. L.
Abstract: Nitrogen (N)‐fixing trees fulfil a unique and important biogeochemical role in forests through their ability to convert atmospheric N2 gas to plant‐available N. Due to their high N fixation rates, it is often assumed that N‐fixing trees facilitate neighbouring trees and enhance forest growth. This assumption is supported by some local studies but contradicted by others, leaving the overall effect of N‐fixing trees on forest growth unresolved. Here we use the US Forest Service's Forest Inventory and Analysis database to evaluate the effects of N‐fixing trees on plot‐scale basal area change and individual‐scale neighbouring tree demography across the coterminous US. First we discuss the average trends. At the plot and individual scales, N‐fixing trees do not affect the relative growth rates of neighbouring trees, but they facilitate recruitment and inhibit survival rates, suggesting that they are drivers of tree turnover in the coterminous US. At the plot scale, N‐fixing trees facilitate the basal area change of non‐fixing neighbours. In addition to the average trends, there is wide variation in the effect of N‐fixing trees on forest growth, ranging from strong facilitation to strong inhibition. This variation does not show a clear geographical pattern, though it does vary with certain local factors. N‐fixing trees facilitate forest growth when they are likely to be less competitive: under high N deposition and high soil moisture or when neighbouring trees occupy different niches (e.g. high foliar C:N trees and non‐fixing trees). Synthesis . N‐fixing trees have highly variable effects on forest growth and neighbour demographics across the coterminous US. This suggests that the effect of N‐fixing trees on forest development and carbon storage depends on local factors, which may help reconcile the conflicting results found in previous localized studies on the effect of N‐fixing trees on forest growth. Abstract : N‐fixing trees have highly variable effects on forest growth and neighbour demographics across the coterminous US. This suggests that the effect of N‐fixing trees on forest development and carbon storage depends on local factors, which may help reconcile the conflicting results found in previous localized studies on the effect of N‐fixing trees on forest growth.